NUTRITIONAL EVALUTION OF FISH SOLUBLES - AMMU, K; STEPHEN, JOSE; ANTONY, P D (Fishery Technology, 2017)
This paper reports the results of a preliminary study on the biochemical composition and nutritional charactersitics of fish solubles from oil sardines (Sardinella longiceps) and white tailed pink perch (Nemipterus japonicus). The nutritional quality of sardine solubles has been evaluated by feeding trials using albino rats also. The studies have shown that compared to a control group of rats whose diet had casein as the sole source of protein, a group of rats in whose diet dried sardine solubles replaced half of the casein, had a noticeably higher growth rate. This higher growth rate was not prominent in the early stages of growth (4-7 weeks). But, during later stages (7-10 weeks), solubles incorporated diet supported a distinctly higher growth rate.This effect was more pronounced in female rats (17% over the control group) compared to the male rats (4% over the control group). Fish solubles are found to be poor sources of essential amino acids. Thus, the observed increase in growth rate is higher than the rate expected from the amino acid make up. This probably supports the view expressed by workers elsewhere that fish solubles contain some unidentified growth factors.